Linguistic Interference and Structural Complexity in Arabic as a Second Language: Evidence from Turkish Learners - Syah, Harif Hidayat; Madjid, Muh. Naim; Güler, Ismail; Azmi, Nafizatul (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
Abstract This explanatory sequential mixed-methods study investigated the linguistic challenges faced by Turkish learners of Arabic at the Department of Arabic Language and Rhetoric, Bursa Uludağ University, Turkey, in acquiring Arabic as a second language. Quantitative data from 52 students, collected via Likert-scale surveys, revealed varying levels of difficulty across four linguistic domains. Phonology (mean = 2.64, 52.85%) and morphology (mean = 2.77, 55.46%) showed moderate difficulty, while syntax (65.67%) and semantics (68.40%) demonstrated greater difficulty. Qualitative data from 20 students identified key obstacles, including phonological interference with emphatic consonants, morphological challenges in verb conjugation, syntactic interference from the Turkish L1, and semantic ambiguity in polysemous terms. The findings suggest that L1 transfer, structural complexity, and prior learning experiences have a significant impact on the acquisition of Arabic. The study concludes by proposing targeted educational interventions that leverage students’ strengths in syntax and semantics while providing greater emphasis on the challenging phonological and morphological aspects.